Fintech and medical expenses: What social workers should know. (21st April 2023) - Despard, Mathieu; Hageman, Sally A.; Ahmad, Maudia
ABSTRACT: Individuals who cannot afford out of pocket medical expenses may reduce health care use, resulting in poorer health outcomes. To ease the situation, employers turn to financial technology ("fintech") health care credit applications. We examine whether an employer-sponsored credit fintech application (MedPut) helps employees manage medical expenses. Results of the analysis of variance (ANOVA) and probit regression models reveal MedPut users did worse financially and delayed health care due to cost more often than employees who did not use MedPut. Results may inform social work policy and direct practice perspectives on fin-tech and medical expenses.